Interview with Raquel Gutiérrez Aguilar - Do, Sustain, Fight: community production, feminisms and territory as a political entity (PerCursos, 2025)
Interview with Raquel Gutiérrez Aguilar - Do, Sustain, Fight: community production, feminisms and territory as a political entity